The influence of institutions on venture capital: How transaction costs, uncertainty, and change affect new ventures - Felix Hoch; Todor S. Lohwasser (Westfälische Wilhelms-Universität Münster, Institut für Organisationsökonomik, 2019)
Institutional dynamics and uncertainty in a country are crucial considerations for investors when searching for venture capital opportunities. International entrepreneurship literature has focused on the impact of unidimensional measures of institutions, despite that institutional environments undergo substantial and continuous changes in multiple dimensions. This study connects literature on the institution-based view and transaction cost economics by examining the effects of reduced transaction costs and uncertainty as institutional outcomes on entrepreneurial activities. Empirical results from 85,711 ventures in 120 countries during the period from 1996 to 2018 show that ventures raise higher funding in countries with (1) generally lower transaction costs that are not constrained by overregulation, (2) higher uncertainty, and (3) institutional environments undergoing change. Funded ventures are more likely to survive in countries with (1) lower transaction costs, (2) lower uncertainty, and without (3) general or (4) disruptive institutional change. Hence, we promote a dynamic perspective for investors and founders when assessing entrepreneurial opportunities in heterogeneous countries since institutional effects driven by uncertainty and transaction costs depend on the individual business purpose. – – Die institutionelle Dynamik und Unsicherheit in einem Land sind entscheidende Faktoren für Investoren bei ihrer Suche nach riskanten Beteiligungsmöglichkeiten. Die internationale Entrepreneurship-Literatur hat sich auf die Auswirkungen eindimensionaler Messungen von Institutionen konzentriert, obwohl sich das institutionelle Umfeld in mehreren Dimensionen stark und kontinuierlich verändert. Diese Studie verbindet Literatur zur institutionenbasierten Sichtweise und Transaktionskostenökonomie, indem sie die Auswirkungen reduzierter Transaktionskosten und Unsicherheiten als institutionelle Ergebnisse auf unternehmerische Aktivitäten untersucht. Empirische Ergebnisse von 85.711 Unternehmen in 120 Ländern im Zeitraum von 1996 bis 2018 zeigen, dass Startups in Ländern mit (1) generell niedrigeren Transaktionskosten, die nicht durch Überregulierung eingeschränkt sind, (2) höherer Unsicherheit und (3) sich verändernden institutionellen Rahmenbedingungen mehr Mittel einsammeln. Bereits finanzierte Startups überleben eher in Ländern mit (1) niedrigeren Transaktionskosten, (2) geringerer Unsicherheit und ohne (3) allgemeinen oder (4) disruptiven institutionellen Wandel. Daher vertreten wir eine dynamische Perspektive für Investoren und Gründer bei der Beurteilung unternehmerischer Chancen in heterogenen Ländern, da institutionelle Effekte, die von Unsicherheit und Transaktionskosten getrieben werden, vom jeweiligen Geschäftszweck abhängen.
Keywords: D02; D23; G24; L26; M13; O57; P48; 650